The Effectiveness of Using Audio-Visual Media in The Learning Process of Islamic Culture History (SKI) Subject at MAN 1 Mandailing Natal - Hanida, Rahmi Seri; Barus, Muhammad Irsan; Lubis, Nur Atikah (Medan Resource Center, 2022)
This research aims to describe the effectiveness of using audio-visual media in the SKI learning process. This type of research is qualitative research which is included in the type of qualitative research that is descriptive qualitative. This study uses interview and observation data collection techniques. While the technique of guaranteeing the validity of the research data, namely, triangulation of sources, techniques, and time. Then the data analysis is done by reducing the data, presenting the data, and drawing conclusions. Based on the results of the research, it can be concluded that using audio-visual media in the SKI learning process at MAN 1 Mandailing Natal is considered quite good and effective. This is evident from the results of the observation sheet testing conducted on three SKI subject teachers at MAN 1 Mandailing Natal reaching scores ranging from 83.3%, 91.6%, and 93.2%. Furthermore, the results of the interviews showed that the SKI learning process becomes more interesting and easy to understand, the classroom atmosphere is also conducive and students are not easily bored and are more enthusiastic in the learning process. Then the attention of students is focused on the material discussed in learning and is able to generate student understanding which is contained in student records and the ability of students to answer and reiterate learning materials appropriately.